2010
DOI: 10.1016/j.cub.2010.04.054
|View full text |Cite
|
Sign up to set email alerts
|

A Gene-Specific Requirement of RNA Polymerase II CTD Phosphorylation for Sexual Differentiation in S. pombe

Abstract: Thus, the S2P polymerase plays a specific, regulatory role in cell differentiation through the induction of ste11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
106
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 59 publications
14
106
1
Order By: Relevance
“…1B). We also constructed a CTD composed of nine tandem copies of a 12-mer element, (YSPTSPSYSPAA) 9 , and found that this CTD sustained apparently normal growth at all temperatures (Fig. 1B) The minimal coding decapeptide brackets two Pro3 and Ser5 residues.…”
Section: Resultsmentioning
confidence: 99%
“…1B). We also constructed a CTD composed of nine tandem copies of a 12-mer element, (YSPTSPSYSPAA) 9 , and found that this CTD sustained apparently normal growth at all temperatures (Fig. 1B) The minimal coding decapeptide brackets two Pro3 and Ser5 residues.…”
Section: Resultsmentioning
confidence: 99%
“…While an overwhelming majority of detectable Ser2-P is absent with loss of activity of the Ctk1 homolog, Lsk1, 36,41 recent data using analog sensitive mutants has also shown that fission yeast Cdk9 is responsible for some level of Ser2-P. [41][42][43] Regulation of yeast Ser2 kinases Mirroring their roles in Ser2 phosphorylation, both Ctk1 and Bur1 are associated with elongating Pol II by chromatin immunoprecipitation (ChIP), 32,44,45 and this has been shown genome wide for Ctk1. 46 In yeast, these kinases appear to be recruited to loci through general mechanisms, rather than genespecific factors.…”
Section: Positive Elongation Factors: Pol II Ctd Serine 2 Kinasesmentioning
confidence: 99%
“…The latter scenario applies to the Ser2 coding letter, insofar as a heterothallic haploid fission yeast rpb1-S2A mutant can grow vegetatively, but is unable to mate with heterothallic WT cells of either mating type, i.e., S2A is sterile. Sterility results from the inability of S2A cells to induce expression of the Ste11 transcription factor that triggers the meiotic sexual differentiation pathway (5,6,8). Microarray analyses of the transcriptome of S2A cells vs. WT highlighted ≥1.5-fold changes in the expression level of many meiotically regulated genes (5,9).…”
Section: Significancementioning
confidence: 99%
“…Sterility results from the inability of S2A cells to induce expression of the Ste11 transcription factor that triggers the meiotic sexual differentiation pathway (5,6,8). Microarray analyses of the transcriptome of S2A cells vs. WT highlighted ≥1.5-fold changes in the expression level of many meiotically regulated genes (5,9). The Ser2 requirement for transcription during sexual differentiation was bypassed by subtracting Ser7, suggesting that imbalance in the phosphorylation array, not absence of a CTD-PO 4 cue, underlies a CTD-associated pathology (6).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation